The collected writings of John Maynard Keynes : vol. 8, a treatise on probability - Keynes, John Maynard (London : MacMillan for the Royal Economic Society, 1973)
This definitive edition contains all Keynes's published writings, including less accessible articles and letters to the press, as well as previously unpublished speeches, government memoranda and minutes, drafts and economic correspondence. No other writer in this century has done more than Maynard Keynes to change the ways in which economics is taught written. No other economist has done more to change the ways in which nations conduct their economic and financial affairs. The Collected Writings are indispensable to all economists. They are a vital reference work for students, academics and professionals alike.
Includes index.
Includes bibliographical references: p. 473-506.
rpm 07/11/2017
Loans
Keywords: Economics; Keynesian economics; Mathematical statistics; Probabilities